Pengaruh Environmental, Social, dan Governance terhadap Profitabilitas pada Perusahaan terdaftar di BEI 2021 - Gharchia, Shalsa Ellya De; Mindosa, Bonnie (Jurnal Manajemen, 2023)
The Sustainable Development Goals (SDGs) are a global action plan approved by world leaders, including Indonesia. In an effort to support the implementation of Environmental, Social, and Governance (ESG) practices, particularly in Indonesia, the Indonesia Stock Exchange has launched a new index called IDX ESG Leaders. This index comprises 30 companies that have good ESG assessments and standards. However, despite being intended as a guide for investors, the index has not shown satisfactory performance. Based on this phenomenon, the author decided to choose the topic of the impact of ESG performance on the financial performance of companies listed on the Indonesia Stock Exchange in 2021. The underlying theories for this research include agency theory, legitimacy theory, and stakeholder theory. The concepts used include profitability, measured using return on assets as a proxy for financial performance, and ESG performance measured through Refinitive ESG Score. The research objects include all companies listed on the Indonesia Stock Exchange in 2021. Sampling was done using non-probability sampling techniques and purposive sampling methods. The analysis method used includes descriptive analysis, classical assumption tests, determination coefficients, F-tests, and t-tests for multiple linear regression analysis with the assistance of SPSS 25. Based on the t-test results, it was found that environmental performance has a positive and significant impact on profitability, while social and governance performance does not have a significant influence on profitability. The results of this research are expected to encourage companies in Indonesia to pay attention to and implement the values found in ESG.